EFEKTIVITAS MEDIA POWERPOINT DALAM MENINGKATKAN PEMAHAMAN SANTRI TERHADAP KITAB ALFIYAH DI PONDOK PESANTREN MAMBAUL ULUM KEDOK TUREN MALANG - Robithatus Zahroh; Ahmad Fauzi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
this study aims to explain how effective the use of PowerPoint media is in improving students' understanding of learning the Book of Alfiyah at the Mambaul Ulum Kedok Turen Islamic Boarding School. The method applied in this study is qualitative descriptive with data collection through interviews, observations, and documentation. This approach was chosen to get a clear picture of the teaching and learning process that occurs and the reaction of students to the use of digital media. The results of the study show that PowerPoint has a significant role in helping students understand nahwu material which is often complex. The presentation of the material through rule points, basic tables, i'rab examples, and explanatory schemes makes the material easier to digest and less confusing. The use of PowerPoint also contributes to increasing students' attention, clarifying the learning flow, and shortening the time for explanations because the material is presented in a concise and structured manner. Students became more active in taking notes and following explanations from the ustadz. However, there are several challenges that arise such as the readiness of technological devices, the quality of projections, and the ability of ustadz to use digital media. However, these challenges do not reduce the main benefits obtained during the learning process. Overall, the application of PowerPoint has proven to be effective in supporting the teaching of the Book of Alfiyah and can be used as an alternative media that contributes to improving students' understanding better without eliminating pesantren values.